Kant's Nonideal Theory of Politics - Huseyinzadegan, Dilek (Northwestern University Press, 2019)
"Kant's Nonideal Theory of Politics" argues that Kant's political thought must be understood by reference to his philosophy of history, cultural anthropology, and geography. The central thesis of the book is that Kant's assessment of the politically salient features of history, culture, and geography generates a nonideal theory of politics, which supplements his well-known ideal theory of cosmopolitanism. This novel analysis thus challenges the common assumption that an ideal theory of cosmopolitanism constitutes Kant's sole political legacy. Dilek Huseyinzadegan demonstrates that Kant employs a teleological worldview throughout his political writings as a means of grappling with the pressing issues of multiplicity, diversity, and plurality--issues that confront us to this day. "Kant's Nonideal Theory of Politics" is the first book-length treatment of Kant's political thought that gives full attention to the role that history, anthropology, and geography play in his mainstream political writings. Interweaving close textual analyses of Kant's writings with more contemporary political frameworks, this book also makes Kant accessible and responsive to fields other than philosophy. As such, it will be of interest to students and scholars working at the intersections of political theory, feminism, critical race theory, and post- and decolonial thought--Provided by publisher.